IMPLEMENTASI METODE STEREO VISION PADA ROBOT TEMPUR CIA VERSI N2MR3 DENGAN MENGGUNAKAN DUA KAMERA - Nadhif Misbachul Hidayat; Nur Rachman Supadmana Muda; M. M. Hudha (Jurnal Telkommil, 2021)
In the 4.0 era, which is progressing towards the 5.0 era, many studies have been carried out on visual sensing in robots. Which has a function as monitoring the movement of robots, especially in the scope of defense in the military. Technological developments in military defense equipment play an important role in supporting the defense of the country's territory. One of them is the development of sensing systems on robots, there are many methods to decide the view of enemy targets against weapons. One of them using the triangulation distance measurement method with the help of a stereo vision camera. This method has advantages in the combat robot system, which is that it can reduce people casualties caused by direct weapon contact with the enemy on the battlefield, especially in urban areas, while the principle of this study is to adopt the similarity of the human eye work system, this method requires a least of two images to get information coordinates the target distance to the camera. Then, we can process the distance information to decide the position of the target against the weapon, while the distance function is carried out to place the robot to take measures. From this background, the author wants to build a visual sensing system using stereo vision. Two webcams with 1080HD resolution each are placed parallel to the combat robot. From the images captured by the two cameras, it can observe the comparison gap between the position of the object with the term disparity, while the results of the disparity are usually used to calculate the distance of the real object and each camera has a viewpoint that can be known, so the distance of the object can be calculated by the more method of triangulation. The results show that the error between the real and the detected distance is 5% and that the camera resolution influences reducing the error.